Systemic lupus erythematosus exacerbation following cessation of belimumab treatment. (3rd March 2016) - Furer, V; Zisman, D; Pokroy-Shapira, E; Molad, Y; Elkayam, O; Paran, D
Abstract : Objectives: Belimumab has recently been approved for the treatment of systemic lupus erythematosus (SLE) refractory to standard therapy. Following one case of an SLE flare after cessation of belimumab, we hypothesized that this might lead to a rebound phenomenon and possible exacerbation of SLE. Method: Members of the Israeli Society of Rheumatology were contacted by e-mail and asked to report cases of an SLE flare following cessation of belimumab treatment. Results: Three cases of SLE patients who experienced a severe SLE flare following cessation of belimumab therapy were reported. In all cases, belimumab was given as treatment for active mucocutaneous manifestations and/or polyarthritis with improvement in all three patients, one of whom achieved disease remission. In all three cases, patients experienced a severe flare in previously uninvolved major organ systems, including one case of class IV lupus nephritis accompanied by a new-onset severe headache with elevated cerebrospinal fluid (CSF) protein and white matter lesions on brain magnetic resonance imaging (MRI), one case of severe pneumonitis and haemolytic anaemia, and one case of a systemic flare, fatigue, arthritis, and severe abdominal pain. Conclusions: Belimumab therapy has been shown to be beneficial in the management of active SLE, mostly in patients with mucocutaneous and musculoskeletal manifestations. We suggest a possible rebound effect following cessation of belimumab that could be due to an increase in B-cell activating factor (BAFF) levels and lead to a disease flare. Future assessment of BAFF levels in patients stopping belimumab therapy and clinical correlation may support this hypothesis. Further studies are needed to confirm this observation.